The Global Costs of Protectionism - Kutlina-Dimitrova, Zornitsa; Lakatos, Csilla (World Bank, Washington, DC, 2017)
This paper quantifies the wide-ranging costs of potential increases in worldwide barriers to trade in two scenarios. First, a coordinated global withdrawal of tariff commitments from all existing bilateral/regional trade agreements, as well as from unilateral preferential schemes coupled with an increase in the cost of traded services, is estimated to result in annual worldwide real income losses of 0.3 percent or US$211 billion relative to the baseline after three years. An important share of these losses is likely to be concentrated in regions such as East Asia and Pacific and Latin America and the Caribbean which together account for close to one-third of the global decline in welfare. Highlighting the importance of preferences, the impact on global trade is estimated to be more pronounced, with an annual decline of 2.1 percent or more than US$606 billion relative to the baseline if these barriers stay in place for three years. Second, a worldwide increase in tariffs up to legally allowed bound rates coupled with an increase in the cost of traded services would translate into annual global real income losses of 0.8 percent or more than US$634 billion relative to the baseline after three years. The distortion to the global trading system would be significant and result in an annual decline of global trade of 9 percent or more than US$2.6 trillion relative to the baseline in 2020.